Awareness, knowledge and breast cancer screening practices among IIUM non-academic staff - Abdul Mutalib, Aaina Mardhiah; Moey, Soo Foon; Kamarudin, Nur Nadira Aiza (IIUM Press, 2019)
In Malaysia, breast cancer is the commonest cancer among women indicating that early diagnosis and screening practice is important to increase the survival rate. Breast self-examination (BSE), clinical breast examination (CBE) and mammography are the main screening practices for breast cancer. Knowledge and awareness of breast cancer can play an important role in aiding early detection of breast cancer. Little is known about the knowledge of breast cancer and screening practices among the non-academic staff in IIUM, Kuantan. As such this study aims to determine the knowledge and screening practices of breast cancer amongst the non-academic staff at the International Islamic University Malaysia (IIUM), Kuantan Campus. A cross-sectional study was conducted on 100 non-academic staff from ten different departments in IIUM, Kuantan from March to April 2017. Data were collected using a self-administered questionnaire on knowledge of breast cancer and screening practices. The relationship between socio-demographic characteristics and knowledge of breast cancer and breast cancer screening practices were carried out using chi-square. No significant difference was found between knowledge of breast cancer and socio-demographic factors. However significant relationships were found between the age of respondents and BSE as well as the level of education of respondents and CBE. Most non-academic staff possessed an average level of knowledge on breast cancer and screening practices due to possibly ease of access to information. Low performance of breast screening practices was indicated possibly due to lack of awareness, the misconception of the need and benefits derived from such screening practices